Bimetal nano-enzyme as well as preparation method and application thereof

By designing the bimetallic nanozyme Fe-Ni@Ti3C2Tx, combining single atomic and bimetallic catalytic mechanisms, the problem of single-unit catalytic mechanism and low signal efficiency is solved, and efficient and safe hydrogen peroxide detection is achieved, suitable for multi-field applications .

CN119140094APending Publication Date: 2024-12-17MUDANJIANG MEDICAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410905375.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-08
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

In the prior art, there are few researches on multi-enzyme active nanoenzymes based on MXene, and the catalytic mechanism is single, and the efficiency of catalytic and signal amplification needs to be improved, especially in the detection of H2O2 in dairy products, there are problems of safety hazards and low detection efficiency.

Method used

Design and prepare a bimetallic nanoenzyme, and prepare Fe-Ni@Ti3C2Tx nanoenzyme through acid etching and ultrasonic methods, combining the catalytic mechanism of single-atom nanoenzyme and bimetallic nanoenzyme to achieve efficient catalytic and signal amplification, for use in Fast and sensitive detection of hydrogen oxide.

Benefits of technology

It has achieved harmless, low-cost, fast and real-time monitoring of hydrogen peroxide detection, and is widely used in biochemical detection, anti-tumor treatment, environmental engineering and food supervision, improving reaction efficiency and detection sensitivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119140094A_ABST
    Figure CN119140094A_ABST
Patent Text Reader

Abstract

The invention relates to a bimetallic nano-enzyme as well as a preparation method and application thereof, and belongs to the technical field of sensors. The preparation method of the bimetallic nano-enzyme comprises the following steps: S1, carrying out etching reaction on MAX by adopting an acid etching solution, and centrifuging and washing to obtain an MXene solution; and S2, carrying out stirring reaction on an iron source and a nickel source in an MXene solution, and carrying out ultrasonic treatment to obtain the bimetallic nano-enzyme. The bimetallic nano-enzyme has peroxidase-like activity and oxidase-like activity, combines the advantages of monatomic nano-enzyme, bimetallic nano-enzyme and dual-enzyme cascade catalysis, and realizes harmless, low-cost, rapid and sensitive and real-time monitoring and detection of hydrogen peroxide by constructing a sensor based on the bimetallic nano-enzyme material with dual-enzyme activity. The method can be widely applied to multiple fields of biochemical detection, anti-tumor treatment, environmental engineering, food supervision and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of sensors, and in particular relates to a bimetallic nanozyme and a preparation method and application thereof. Background Art

[0002] Dairy products are rich in nutrients and have the functions of enhancing the body's immunity, improving memory and attention, etc., and have become a necessity in people's daily life. H2O2, also known as hydrogen peroxide, is widely used as a disinfectant, preservative and bleaching agent in dairy products because of its strong oxidizing properties and excellent bactericidal properties. Studies have shown that excessive H2O2 can reduce the body's antioxidant capacity, damage cells, accelerate human aging, etc., and then lead to cancer, cardiovascular disease and central nervous system diseases. In recent years, dairy product safety incidents have occurred frequently. In order to save costs and make huge profits, many businesses illegally add industrial-grade H2O2 or add food-grade H2O2 beyond the standard to achieve the effect of disinfection, preservation and change the appearance of food. Therefore, it is crucial to achieve sensitive and rapid detection of H2O2 in dairy products. At present, there are H2O2 colorimetric detection kits, but most of them use easily made-toxin reagents such as acetone and concentrated hydrochloric acid, which are harmful to the human body and the environment. There are also shortcomings such as narrow linear range and inability to perform high-throughput detection. How to avoid the use of toxic and harmful substances during the detection process and how to improve the convenient detection of H2O2 in milk with high sensitivity and high specificity have become urgent issues to be solved in the field of H2O2 detection.

[0003] Nanozymes are chemically synthesized nanomaterials with natural enzyme activity and are often used for H2O2 detection. Compared with natural enzymes, nanozymes have not only enzyme-like activity, but also nanomaterial characteristics such as easy synthesis, easy storage, high stability and low cost. Different nanomaterials, including carbon-based nanomaterials, transition metal oxides and metals, have successfully simulated various natural enzymes such as peroxidase, oxidase, catalase and superoxide dismutase. Therefore, nanozymes are widely used in biochemical detection, anti-tumor therapy, environmental engineering, food regulation and other aspects. Nanozymes with dual activities are more conducive to practical applications. Among them, nanozymes with both peroxidase-like and oxidase-like activities belong to a relatively important category. They can cleverly form a cascade reaction system between the two enzyme activities, achieve self-sufficiency of intermediates, form a closed-loop reaction, and greatly improve the reaction efficiency.

[0004] Two-dimensional layered nanomaterials such as MXene, black phosphorus, graphitized carbon nitride, etc. have shown great application potential in the field of nanozymes due to their large specific surface area, excellent physical and chemical properties and unique nanosheet structure. MXene is a two-dimensional material with a graphene-like structure, composed of transition metal carbides, nitrides or carbonitrides. The chemical formula is M n+ 1X n T x, where M is a pre-transition metal element, X is carbon, nitrogen, nitrogen, T x Surface functional groups, such as -F, -Cl, =O, -OH, etc. MXene has been widely used in biomedicine, energy storage, catalysis, sensors and other fields due to its unique physical and chemical properties, such as large specific surface area, good electrical conductivity, excellent catalytic performance and easy functionalization. Ti3AlC2 is a common MXene material. The special hexagonal crystal system and layered structure give Ti3AlC2 high electrical conductivity, high thermal conductivity, easy processing, corrosion resistance and good thermal shock resistance. However, defects such as easy oxidation, easy stacking of layers and poor biocompatibility of Ti3AlC2 limit its application. Summary of the invention

[0005] Therefore, the technical problem to be solved by the present invention is to overcome the existing problems in the prior art based on MXene (Ti3C2T x ) There are few studies on nanozymes with multi-enzyme activities, the catalytic mechanism of nanozymes is single, and the efficiency of nanozyme catalysis and signal amplification needs to be improved.

[0006] To solve the above technical problems, the present invention provides a bimetallic nanozyme and its preparation method and application. The bimetallic nanozyme based on MXene has the advantages of single-atom nanozyme, bimetallic nanozyme and bimetallic cascade catalysis, and can achieve efficient catalysis and signal amplification through various mechanisms. It can be widely used in biochemical detection, anti-tumor treatment, environmental engineering, food supervision and other fields. It lays a foundation for the design and simple preparation of bimetallic nanozymes with multiple enzyme activities, and also provides a new direction for the structural design and multifunctional properties of MXene.

[0007] The first object of the present invention is to provide a method for preparing a bimetallic nanozyme, comprising the following steps:

[0008] S1, etching MAX with an acid etching solution, and obtaining a MXene solution by centrifugation and washing;

[0009] S2, the iron source and the nickel source are stirred and reacted in the MXene solution described in S1, and the bimetallic nanozyme is obtained by ultrasound.

[0010] In one embodiment of the present invention, in S1, the acid etchant is obtained by mixing LiF and HCl solutions; the mass volume ratio of the LiF and HCl solutions is (3-3.5:40) g / mL; and the concentration of the HCl solution is 9 mol / L-12 mol / L.

[0011] In one embodiment of the present invention, in S1, the mass volume ratio of the MAX and the acid etching solution is (2:40-45) g / mL.

[0012] In one embodiment of the present invention, in S1, the temperature of the etching reaction is 40° C.-50° C., and the time is 36 h-48 h.

[0013] In one embodiment of the present invention, in S2, the iron source is ferric chloride; the nickel source is nickel chloride.

[0014] In one embodiment of the present invention, in S2, the mass ratio of the iron source to the nickel source is 5.5-7.5:9; the mass volume ratio of the iron source to the MXene solution is (5.5-7.5:10) g / mL.

[0015] In one embodiment of the present invention, in S2, the speed of the stirring reaction is 320 rpm-380 rpm, and the time is 8 min-12 min; the power of the ultrasound is 75 W-85 W, and the time is 28 min-32 min.

[0016] The second object of the present invention is to provide a bimetallic nanozyme prepared by the method described above.

[0017] The third object of the present invention is to provide an application of the bimetallic nanozyme in hydrogen peroxide detection.

[0018] The fourth object of the present invention is to provide a hydrogen peroxide sensor, which contains the bimetallic nanozyme.

[0019] The technical solution of the present invention has the following advantages over the prior art:

[0020] (1) The bimetallic nanozyme of the present invention has an enzyme cascade catalytic system, which greatly improves the reaction efficiency; the Fe and Ni bimetallics exist in a variety of valence states in the nanozyme, and can simultaneously achieve high-efficiency catalysis through a variety of mechanisms, thereby amplifying the signal. This bimetallic nanozyme lays the foundation for the design and simple preparation of bimetallic nanozymes with multiple enzyme activities.

[0021] (2) The bimetallic nanozyme of the present invention has peroxidase-like activity and oxidase-like activity, and combines the advantages of single-atom nanozymes, bimetallic nanozymes, and dual-enzyme cascade catalysis. x ) material to construct sensors that realize harmless, low-cost, rapid, sensitive and real-time monitoring and detection of hydrogen peroxide, and can be widely used in biochemical testing, anti-tumor treatment, environmental engineering, food supervision and other fields. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to make the content of the present invention more clearly understood, the present invention is further described in detail below according to specific embodiments of the present invention in conjunction with the accompanying drawings, wherein:

[0023] Figure 1 This is a process flow chart of the preparation of the bimetallic nanozyme of Example 1 of the present invention;

[0024] Figure 2 The bimetallic nanozyme Fe-Ni@Ti3C2T of Test Example 1 of the present invention x Characterization diagram; AB is Fe-Ni@Ti3C2T x TEM image, CD is Fe-Ni@Ti3C2T x HRTEM image of Fe-Ni@Ti3C2T x EDS diagram of

[0025] Figure 3 The bimetallic nanozyme Fe-Ni@Ti3C2T of Test Example 2 of the present invention x XRD pattern of

[0026] Figure 4 The bimetallic nanozyme Fe-Ni@Ti3C2T of Test Example 2 of the present invention x XPS graph of

[0027] Figure 5 Fe-Ni@Ti3C2T of Test Example 3 of the present invention x 、Ni@Ti3C2T x and Fe@Ti3C2T x Comparison of enzyme activities;

[0028] Figure 6 Fe-Ni@Ti3C2T of Test Example 4 of the present invention x Comparison of enzyme activity of HPR and HPR;

[0029] Figure 7 Fe-Ni@Ti3C2T of Test Example 5 of the present invention x Verification of dual enzyme activity;

[0030] Figure 8 This is the optimization of the sensor experimental conditions of Test Example 6 of the present invention. DETAILED DESCRIPTION

[0031] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. It should be understood that the specific embodiments are only used to explain the present invention, but the embodiments are not intended to limit the present invention.

[0032] In the present invention, unless otherwise explained, technical and scientific terms used in the present invention have the same meanings as commonly understood by those skilled in the art to which the present invention belongs.

[0033] In the present invention, unless otherwise stated, the term "and / or" used in the present invention includes any and all combinations of one or more of the associated listed items.

[0034] In the present invention, unless otherwise stated, the experimental methods used in the embodiments of the present invention are conventional methods unless otherwise stated, and the materials, reagents, etc. used are all commercially available unless otherwise stated.

[0035] Example 1

[0036] Reference Figure 1 As shown, the bimetallic nanozyme and the preparation method thereof of the present invention specifically include the following steps:

[0037] S1, single few-layer Ti3C2T x Preparation of nanosheet solution: LiF (3.2 g) was added to HCl solution (12 mol / L, 40 mL) and heated to 45 ° C and maintained for 10 min under stirring to obtain an acid etching solution; MAX (Ti3AlC2, 2 g) was added to the above acid etching solution and magnetically stirred at 45 ° C for 48 h; then poured into a centrifuge tube, centrifuged for 5 min, rinsed three times with dilute HCl solution (2 mol / L), and then rinsed with ultrapure water until the pH of the upper layer of the solution was close to 6 (centrifuged at 3500 rpm for 5 min to allow the liquid to drip and leave the precipitate); then the mixture was poured into a gas collection bottle and ultrasonically treated for 1 h under nitrogen and ice bath conditions. Finally, the mixture was poured into a centrifuge tube and centrifuged for 45 min; the upper layer of the black liquid was a single few-layer Ti3C2T x The nanosheet solution was sealed and stored in a 4 °C refrigerator until use.

[0038] S2, bimetallic nanozyme Fe-Ni@Ti3C2T x Preparation: 6 mg FeCl3·6H2O and 9 mg NiCl2·6H2O were added to 10 mL single few-layer Ti3C2T x The nanosheet solution was stirred at 350 rpm for 10 min, and then ultrasonicated at 80 W for 30 min to obtain the bimetallic nanozyme Fe-Ni@Ti3C2T x , store the synthetic material in a light-proof refrigerator at 4°C for later use.

[0039] Comparative Example 1 is basically the same as Example 1, except that the preparation of nanozyme

[0040] S1, single few-layer Ti3C2T xThe preparation of the nanosheet solution is the same as in Example 1;

[0041] S2, single metal nanozyme Fe@Ti3C2T x Preparation: Add 6 mg FeCl3·6H2O to 10 mL single few-layer Ti3C2T x The nanosheet solution was stirred at 350 rpm for 10 min, and then ultrasonicated at 80 W for 30 min to obtain the bimetallic nanozyme Fe-Ni@Ti3C2T x , store the synthetic material in a light-proof refrigerator at 4°C for later use.

[0042] Comparative Example 2 is basically the same as Example 1, except that the preparation of nanozymes

[0043] S1, single few-layer Ti3C2T x The preparation of the nanosheet solution is the same as in Example 1;

[0044] S2, Single Metal Nanozyme Ni@Ti3C2T x Preparation: Add 9 mg NiCl2·6H2O to 10 mL single few-layer Ti3C2T x The nanosheet solution was stirred at 350 rpm for 10 min, and then ultrasonicated at 80 W for 30 min to obtain the bimetallic nanozyme Fe-Ni@Ti3C2T x , store the synthetic material in a light-proof refrigerator at 4°C for later use.

[0045] Comparative Example 3

[0046] Horseradish peroxidase (HRP).

[0047] Test Example 1

[0048] The bimetallic nanozyme Fe-Ni@Ti3C2T prepared in Example 1 x The results are as follows Figure 2 As shown. Figure 2 A- Figure 2 B shows that Fe-Ni@Ti3C2T x TEM shows that Fe-Ni@Ti3C2T x The good nanosheet structure is retained, and a large number of Fe and Ni nanoparticles can be observed to be uniformly dispersed in the Ti3C2T x On the nanosheet. Figure 2 C- Figure 2 D It can be seen that there are a lot of bright spots in the HAADF-STEM image, indicating that Fe-Ni@Ti3C2T x There are Fe atoms on Figure 2 It can be seen from E that the energy dispersive X-ray spectroscopy (EDS) measured the Fe-Ni@Ti3C2Tx Elements such as C, Ti, O, Fe, and Ni are evenly distributed.

[0049] Test Example 2

[0050] The bimetallic nanozyme Fe-Ni@Ti3C2T prepared in Example 1 was characterized by XRD and XPS. x The elemental composition and chemical state of the surface are analyzed, and the results are as follows Figure 3-Figure 4 As shown. Figure 3 It can be seen that XRD contains Fe 2+ Compounds and Ni 2+ Compound-related diffraction peaks. Figure 4 It can be seen that XPS shows an obvious peak at 710.4 eV, corresponding to Fe 2P, and an obvious peak at 855.6 eV, corresponding to Ni 2P, further proving that Fe-Ni@Ti3C2T x Fe 2+ Compounds and Ni 2+ Compound.

[0051] Test Example 3

[0052] Based on the following principles: (1) in the TMB / H2O2 system, peroxidase-like enzymes can change TMB from colorless to blue oxTMB; (2) a strong absorption peak will appear at 650nm in the ultraviolet absorption spectrum. x 、Ni@Ti3C2T x and Fe@Ti3C2T x Add 0.5 mL 100 μM H2O2 and 3.5 mL TMB to three test tubes, incubate at 50°C for 13 min, and then measure under UV spectrophotometer (original pH = 3, which is the optimal pH value). Compare the absorbance of the three and the absorption peak at 650 nm. The results are as follows: Figure 5 As shown. Figure 5 It can be seen that Ni@Ti3C2T x 、Fe@Ti3C2T x 、H2O2+TMB+Fe-Ni@Ti3C2T x In the UV-visible spectrum, there is an obvious absorption peak at 650nm, but H2O2+TMB+Fe-Ni@Ti3C2T x The absorbance of the system and the absorption peak at 650nm are much higher than those of Ni@Ti3C2T x and Fe@Ti3C2T x system, indicating that Fe-Ni@Ti3C2T x The enzyme catalytic activity is stronger than that of Ni@Ti3C2Tx and Fe@Ti3C2T x . Combining MAX with nanoparticles, metal particles, etc. can improve its defects of easy oxidation, easy interlayer accumulation, and poor biocompatibility. Functionalized MAX has peroxidase-like activity, which can catalyze H2O2 to generate -OH, and then oxidize TMB to change its color (from colorless to blue). Single-atom nanozymes have unique electronic structures, clear geometric configurations, and high atomic utilization. In Ti3AlC x In the above diagram, the element Fe exists in atomic form, with one Fe atom coordinated with three oxygen atoms. x The strong interaction between Fe and Ni promotes electron transfer, thereby enhancing the peroxidase-like activity. Bimetallic nanozymes can solve the defect of low loading of single-atom nanozymes and enhance the peroxidase-like activity of single-atom nanozymes through synergistic effects. Ni is a transition metal with a small atomic radius, low electronegativity, and multiple valence states. It is easy to lose or capture electrons in the d electron layer. Ni has been designed into a variety of nanozymes due to its strong redox properties, stable chemical properties, and low cost. Therefore, Fe-Ni bimetallic nanozymes may have better performance.

[0053] Test Example 4

[0054] 1 mL of 1.5 mg / mL Fe-Ni@Ti3C2T x and horseradish peroxidase HPR were added to a test tube containing 0.5 mL H2O2 and 3.5 mL TMB, incubated at 50°C for 13 min, and then detected under a UV spectrophotometer (original pH = 3, which is the optimal pH value). The absorbance of the two and the absorption peak at 650 nm were compared. The results are as follows: Figure 6 As shown. Figure 6 It can be seen that at 650nm, Fe-Ni@Ti3C2T x The absorption peak of Fe-Ni@Ti3C2T x The peroxidase catalytic activity of Fe-Ni@Ti3C2T x Based on multiple catalytic mechanisms (single-atom nanozyme catalysis, bimetallic nanozyme catalysis, dual-enzyme cascade catalysis, and Fenton reaction catalysis), it has strong enzyme activity and can replace the currently commonly used horseradish peroxidase HPR. Compared with horseradish peroxidase HPR, it has the advantages of easy storage, stability, low cost, and strong catalytic ability.

[0055] Test Example 5: Verification of Dual Enzyme Activity

[0056] Based on the following principles: (1) In the TMB / H2O2 system, peroxidase-like enzymes can change TMB from colorless to blue oxTMB; (2) oxidase-like enzymes can directly change TMB from colorless to blue oxTMB; (3) When Fe-Ni@Ti3C2T x When it has peroxidase-like activity or oxidase-like activity, a strong absorption peak appears at 650nm in the UV absorption spectrum. This test example explores the x The absorbance was measured by 1 mL of 1.5 mg / mL Fe-Ni@Ti3C2T x , 0.5 mL 100 μM H2O2 and 3.5 mL TMB were combined into the following systems: TMB / H2O2 system, H2O2 / Fe-Ni@Ti3C2T x System, TMB / H2O2 / Fe-Ni@Ti3C2T x System, TMB+Fe-Ni@Ti3C2T x The system was incubated at 50°C for 13 min and then tested under a UV spectrophotometer (the original pH = 3, which is the optimal pH value). The results are as follows: Figure 7 As shown. Figure 7 It can be seen that adding Fe-Ni@Ti3C2T x After that, the colorless TMB turned into blue oxTMB, and an absorption peak much higher than that of other experimental groups appeared at 650nm in the UV absorption spectrum, indicating that Fe-Ni@Ti3C2T x It has strong peroxidase-like activity. TMB+Fe-Ni@Ti3C2T x The absorption peak of the system was also observed at 650nm, but it was lower than that of TMB+H2O2+Fe-Ni@Ti3C2T x system, indicating that Fe-Ni@Ti3C2T x It has oxidase-like activity and can catalyze the oxidation of TMB by O2. The above results show that Fe-Ni@Ti3C2T x It has strong peroxidase-like and oxidase-like activities.

[0057] Test Example 6 Optimization of sensor experimental conditions

[0058] 1 mL of 1.5 mg / mL Fe-Ni@Ti3C2T x Add 0.5mL 100μM H2O2 and 3.5mL TMB mixed solution to obtain Fe-Ni@Ti3C2T x / TMB / H2O2 sensor, the conditions that may affect the sensor detection performance, such as pH, time, and temperature, were optimized. pH optimization: the pH range of the mixed solution of 0.5mL 100μM H2O2 and 3.5mL TMB was adjusted to 2-6, and then 1.5mg / mL Fe-Ni@Ti3C2T x , incubated at 50°C for 13 min and then detected under UV spectrophotometer. The results are as follows Figure 8 As shown in A, the best absorbance is obtained when pH is 3. Time optimization: pH is fixed at 3 and temperature is fixed at 50℃, and Fe-Ni@Ti3C2T x The absorbance of the UV absorption spectrum at 650nm when the reaction time range of the / TMB / H2O2 sensor is 11min-15min is as follows Figure 8 As shown in B, the reaction time was 13 min to obtain the best absorbance. Temperature optimization: pH was fixed at 3, time was fixed at 13 min, and Fe-Ni@Ti3C2T x The absorbance of the / TMB / H2O2 sensor at 650nm of the UV absorption spectrum when the incubation temperature is 20℃-60℃ is as follows: Figure 8 C shows that the best absorbance is obtained when the temperature is 50℃. x The optimal reaction conditions of the / TMB / H2O2 sensor are pH=3, time=13min, and temperature=50℃.

[0059] Test Example 7 Detection of Hydrogen Peroxide by Different Sensors

[0060] Sensor linear range: Fe-Ni@Ti3C2T constructed in test example 6 x / TMB / H2O2 sensor, incubated at 50℃ for 13min, and then tested under UV spectrophotometer (original pH=3, which is the optimal pH value) for 50μM-6000μM hydrogen peroxide concentration, and successfully established a linear relationship between hydrogen peroxide concentration and absorbance value y=0.000118572x+3.84264. x / TMB / H2O2 sensor, after incubation at 50℃ for 13min, was tested under UV spectrophotometer (original pH=3, which is the optimal pH value) for 1μM-7000μM hydrogen peroxide concentration, and verified by y=0.000118572x+3.84264 equation, and it was found that the equation was not applicable, that is, Fe-Ni@Ti3C2T x The detection range of the / TMB / H2O2 sensor is 50μM-6000μM;

[0061] Minimum detection limit: Calculated by dividing the standard deviation of three times the blank concentration of hydrogen peroxide by the slope of the linear equation (3σ / k);

[0062] Fe-Ni@Ti3C2T x The linear range and detection limit of H2O2 detected by the / TMB / H2O2 sensor were compared with those of existing sensors of different types. The results are shown in Table 1:

[0063] Table 1

[0064] sensor Linear range (μM) Detection limit (μM) References <![CDATA[Fe-Ni@Ti3C2T x ]]> 50-6000 14.606 This Work Ag-AuNPs 30-300 18 Zhao et al.2018 <![CDATA[Ag2S-MMT]]> 200-1200 19.16 Liu et al.2016 <![CDATA[Co / Fe / NiO x @NF]]> 200-4000 32.9 Wu et al.2023 <![CDATA[Cu2O / TiO2 / Ti]]> 500-8000 90.5 Wen et al.2017 Pt / NiCo-LDHNCs 1000-9000 760 Cao et al.2021

[0065] As can be seen from Table 1, the sensor of the present application has the lowest detection limit of 14.606 μM, a wide linear range of 50 μM-6000 μM, and the linear range covers low and high concentrations of hydrogen peroxide, which is suitable for the detection of hydrogen peroxide in many fields.

[0066] Test Example 8 Anti-interference capability test

[0067] The specificity of the sensor was evaluated by comparing the absorbance of the sensor to H2O2 in the presence or absence of interfering substances. First, K (100 times the concentration of hydrogen peroxide (10 M)) was added to a mixed solution of 0.5 mL of 100 μM H2O2 and 3.5 mL of TMB. + , Na + , Al 3+ ,Cr 3+ , Li + , Ca 2+ , Mn 2+ , F-, HPO4 2- ,CO3 2- , NO3 - Then add 1.5 mg / mL Fe-Ni@Ti3C2T x , incubated at 50℃ for 13min and then tested under UV spectrophotometer (original pH=3, which is the optimal pH value) to investigate the anti-interference ability of the sensor. The results showed that adding K + , Na + , Al 3+ ,Cr 3+ , Li + , Ca 2+ , Mn 2+ , F-, HPO4 2- ,CO3 2- , NO3 - The mean values ​​of ion absorbance are 3.81567, 3.86867, 3.85, 3.81917, 3.795, 3.8225, 3.87633, 3.798, 3.83117, 0.294, 0.78867, except CO32- and NO 3- Except for the above, other interferences have no significant effect on the detection of H2O2. This is because H2O2 has a strong oxidizing property and CO3 2- and NO3 - Both of them undergo redox reactions with H2O2. In other words, they will not coexist in a real environment. Therefore, the sensor of the present application has excellent specificity.

[0068] Test Example 9: Stability Test

[0069] Fe-Ni@Ti3C2T x The stability of the sensor was investigated by taking different concentrations of H2O2 (100μM, 1000μM, 3000μM) at 0, 1, 2, and 3 weeks after storage at 4°C. 1 mL of 100μM, 1000μM, and 3000μM hydrogen peroxide solution was mixed with 3.5 mL of TMB solution, and then Fe-Ni@Ti3C2T x Add to the above three mixed solutions, incubate at 50°C for 13 minutes, and then detect under UV spectrophotometer (original pH = 3, which is the optimal pH value). The results are shown in Table 2:

[0070] Table 2

[0071] Week 100μM 1000μM 3000μM 0 3.87967 3.95117 4.21917 1 3.865 3.9435 4.21 2 3.859 3.9305 4.18367 3 3.8335 3.90983 4.14633

[0072] As can be seen from Table 2, Fe-Ni@Ti3C2T stored for 0, 1, 2, and 3 weeks x It can detect 100μM, 1000μM, and 3000μM hydrogen peroxide solutions, and the mean difference is small. x The peroxidase activity of Fe-Ni@Ti3C2T x The H2O2 sensor has good stability.

[0073] Test Example 10 Reproducibility Test

[0074] In order to evaluate the reproducibility of the sensor, 9 identical systems were prepared to detect 100μM, 1000μM, and 3000μM H2O2 at the same time. 1mL of 100μM, 1000μM, and 3000μM hydrogen peroxide solution was mixed with 3.5mL TMB solution, and then Fe-Ni@Ti3C2T x Add to the above mixed solution, incubate at 50°C for 13 minutes, and then detect under UV spectrophotometer (original pH = 3, which is the optimal pH value). The results are shown in Table 3:

[0075] Table 3

[0076] frequency 100μM 1000μM 3000μM 1 3.86533 3.92217 4.15883 2 3.8805 3.93 4.16783 3 3.887 3.928 4.16017 4 3.85133 3.94233 4.1625 5 3.89133 3.92067 4.14117 6 3.85183 3.93567 4.14867 7 3.86483 3.95117 4.16183 8 3.85217 3.92233 4.15383 9 3.909 3.92333 4.18467

[0077] As can be seen from Table 3, the relative standard deviations (RSD) of 100 μM, 1000 μM, and 3000 μM H2O2 are relatively small, being 2.23%, 2.44%, and 3.33%, respectively, indicating that the sensor of the present application has good reproducibility.

[0078] Test Example 11 Actual Sample Testing

[0079] In order to evaluate the practicality of the sensor for detecting H2O2 in actual samples, the recovery of H2O2 was analyzed using both blank spike recovery and sample spike recovery methods.

[0080] Blank spike recovery: 1 mL of 500 μM, 1000 μM, and 3000 μM hydrogen peroxide solutions were mixed with 3.5 mL of TMB solution, and then Fe-Ni@Ti3C2T x The mixture was added to the above-mentioned mixed solution, incubated at 50° C. for 13 min, and then detected under a UV spectrophotometer (the original pH = 3, which is the optimal pH value).

[0081] Sample spike recovery: Yili milk purchased from a local supermarket was centrifuged for 2 h, and 500 μM, 1000 μM, and 3000 μM H2O2 were added, respectively. The above solutions were mixed with 3.5 mL TMB solution, and then Fe-Ni@Ti3C2T x Add to the above mixed solution, incubate at 50°C for 13 minutes, and then detect under UV spectrophotometer (original pH = 3, which is the optimal pH value). The results are shown in Table 4:

[0082] Table 4

[0083]

[0084] As can be seen from Table 4, the blank spiked recoveries of the three concentrations were 106.53%, 96.47%, and 101.10%, respectively, and the RSDs were 2.52%, 1.15%, and 1.65%, respectively. The sample spiked recoveries of the three concentrations were 104.47%, 102.67%, and 100.94%, respectively, and the RSDs were 4.98%, 4.59%, and 3.34%, respectively, indicating that the sensor of the present application is suitable for the detection of H2O2 in actual samples.

[0085] Obviously, the above embodiments are merely examples for clear explanation and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.

Claims

1. A method for preparing a bimetallic nanozyme, characterized in that: The following steps are involved: S1, etching MAX with an acid etching solution, and obtaining a MXene solution by centrifugation and washing; S2, the iron source and the nickel source are stirred and reacted in the MXene solution described in S1, and the bimetallic nanozyme is obtained by ultrasound.

2. The method for preparing the bimetallic nanozyme according to claim 1, characterized in that: In S1, the acid etchant is obtained by mixing LiF and HCl solutions; the mass volume ratio of the LiF and HCl solutions is (3-3.5:40) g / mL; and the concentration of the HCl solution is 9 mol / L-12 mol / L.

3. The method for preparing the bimetallic nanozyme according to claim 1, characterized in that: In S1, the mass volume ratio of the MAX and the acid etching solution is (2:40-45) g / mL.

4. The method for preparing the bimetallic nanozyme according to claim 1, characterized in that: In S1, the etching reaction temperature is 40°C-50°C, and the time is 36h-48h.

5. The method for preparing the bimetallic nanozyme according to claim 1, characterized in that: In S2, the iron source is ferric chloride; the nickel source is nickel chloride.

6. The method for preparing the bimetallic nanozyme according to claim 1, characterized in that: In S2, the mass ratio of the iron source to the nickel source is 5.5-7.5:9; the mass volume ratio of the iron source to the MXene solution is (5.5-7.5:10) g / mL.

7. The method for preparing the bimetallic nanozyme according to claim 1, characterized in that: In S2, the rotation speed of the stirring reaction is 320 rpm-380 rpm, and the time is 8 min-12 min; the power of the ultrasound is 75 W-85 W, and the time is 28 min-32 min.

8. A bimetallic nanozyme prepared by the method according to any one of claims 1 to 7.

9. An application of the bimetallic nanozyme as claimed in claim 8 in hydrogen peroxide detection.

10. A hydrogen peroxide sensor, characterized in that: The hydrogen peroxide sensor contains the bimetallic nanozyme according to claim 8.